Investigating the Written Exam Scores’ Prediction Power of TEOG Exam Scores - Hakkı Kontaş; Esen Turan Ozpolat (Institute of Advanced Engineering and Science, 2017)
The purpose of this study was to investigate exam scores’ predicting Transition from Primary to Secondary Education (TEOG) exam scores. The research data were obtained from the records of 1035 students studying at the first term of eighth grade in 2015-2016 academic year in e-school system. The research was on relational screening model. Linear regression model was used for the analysis of data. The analysis results proved that there was a high level significant relationship between exam scores and TEOG exam scores.